Bank stability measures in dual banking system: a critical review / Norzitah Abdul Karim …[et al.] - Abdul Karim, Norzitah; Muhamat, Amirul Afiff; Roslan, Azreen; Syed Alwi, Sharifah Faigah; Jaafar, Mohamad Nizam (Universiti Teknologi MARA Cawangan Selangor, 2019)
The 2007-2009 Global Financial Crisis showed that despite reported as ‘healthy’ financial institution prior to crisis had indeed suffered many problems including liquidity during the crisis. Thus, there is confusion on the healthy financial institutions, leading to loss of confidence on the overall stability of the banking system. Thus, there is an urgent need to review the current measures of financial as well as banking stability. This paper aims to look at the definition of ‘stability’ used in the academic researches and by different regulatory bodies, like International Monetary Fund, Basel Committee for Banking Supervision (BCBS) and central banks in selected countries with dual banking systems. It is then, critically review indicators used as measures of financial as well as banking stability. This review is hope to identify areas of strengths as well as weaknesses of the current measures of stability and serves as foundation for further research in future.